Sleep disturbance after pediatric and adolescent concussion - Wilkes, James; Fedonni, Daniele; Cottone, Jelsia; Arbogast, Kristy B.; Master, Christina L. (Frontiers in Sleep, 2025)
IntroductionSleep disturbances following concussion are common. The goal of this study was to describe subjective reports of sleep disturbances for pediatric and adolescent patients, whether they predict prolonged recovery or moderate the relationship between comorbidities, symptom burden, and recovery.Materials and methodsClinical electronic health record (EHR) data from a prospective concussion registry of patients aged 5–18 were used for this study. Specific demographic and injury characteristics included sex, age, race and ethnicity, previous concussion history, symptom scores, and personal history of mental health diagnoses and sleep problems. Categorical variables were compared with Pearson's chi-squared tests and continuous variables were compared with Kruskal-Wallis rank sum test. Univariate and multivariate logistic regression were used to calculate odds ratios, 95% confidence intervals and p-values for factors associated with prolonged concussion recovery. Interaction terms were created for each comorbidity and sleep changes to test for moderation effects of comorbidities on the relationship between sleep disturbance and prolonged recovery.ResultsA total of 4,469 patients with a concussion were seen within 28 days of injury during the study period and included in analyses, with 3,002 (67%) reporting new sleep disturbance. Those with sleep disturbance differed by sex, age, time from injury to initial visit, Post Concussion Symptom Inventory (PCSI) at initial visit, concussion history, presence of comorbidities, and COI. In the multivariate model, female patients (OR 1.43, 95% CI 1.25–1.64), those with new sleep disturbance (OR 1.37, 95% CI 1.18–1.60), patients without a previous concussion diagnosis (OR 1.31, 95% CI 1.15–1.52), medical history of a learning disability (OR 1.3, 95% CI 1.10–1.67), more days between injury to initial visit (CI 1.08–1.10), and a higher initial PCSI score (OR 1.03, 95% CI 1.03–1.03) had greater odds of prolonged recovery. Interaction terms for moderation effects of comorbidities on the relationship between sleep disturbance and prolonged recovery were not statistically significant.DiscussionNearly 2/3 of concussion patients self-reported changes in sleep after injury, a higher rate than previously reported (51%). Sleep disturbances following concussion were the second strongest predictor of prolonged recovery past 28 days, only behind female sex, and comorbidities did not moderate that relationship.